Reconciling the Greenland ice-core and radiocarbon timescales through the Laschamp geomagnetic excursion - Staff, Richard A.; Koutsodendris, Andreas; Pross, Jörg (Earth and planetary science letters, 2019)
Cosmogenic radionuclides, such as 10Be and 14C, share a common production signal, with their formation in the Earth's upper atmosphere modulated by changes to the geomagnetic field, as well as variations in the intensity of the solar wind. Here, we use this common production signal to compare between the radiocarbon (IntCal) and Greenland ice-core (GICC05) timescales, utilising the most pronounced cosmogenic production peak of the last 100,000 years - that associated with the Laschamp geomagnetic excursion circa 41,000 years ago. We present 54 new 14C measurements from a peat core (‘TP-2005’) from Tenaghi Philippon, NE Greece, contiguously spanning between circa 47,300 and 39,600 cal. BP, demonstrating a distinctive tripartite structure in the build up to the principal Laschamp production maximum that is not present in the consensus IntCal13 calibration curve. This is the first time that a continuous, non-reservoir corrected 14C dataset has been generated over such a long time span for this, the oldest portion of the radiocarbon timescale. This period is critical for both palaeoenvironmental and archaeological applications, with the replacement of Neanderthals by anatomically modern humans in Europe around this time. By placing our Tenaghi Philippon 14C dataset on to the Hulu Cave U-series timescale of Cheng et al. (2018) via Bayesian statistical modelling, the comparison of TP-2005 14C with Greenland 10Be fluxes also implicitly relates the underlying U-series and GICC05 timescales themselves. This comparison suggests that whilst these two timescales are broadly coherent, the IntCal13 timescale contains erroneous structure circa 40,000 cal. BP.